Intelligence matters the CIA, the FBI, Saudi Arabia, and the failure of America's War on Terror - Graham, Bob. (University Press of Kansas, 2008)
Shining much-needed light on areas the 9/11 Commission preferred to keep dark, Intelligence Matters chronicles the efforts of a historic joint House-Senate inquiry to get to the bottom of our intelligence failures on that infamous day in 2001. Originally published in 2004 amid the media circus surrounding The 9/11 Commission Report, it told more than a riveting tale?it also provided an unflinching expos of failure, incompetence, and deceit at the highest levels of our government.
Includes bibliographical references (p. [307]-314) and index.
Keywords: Intelligence service--United States